2022
DOI: 10.1136/bjophthalmol-2021-320448
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative assessment of anterior segment optical coherence tomography capture of disease state in childhood anterior uveitis

Abstract: Background/aimsAnterior segment optical coherence tomography (AS-OCT) assessment of anterior chamber inflammation is an emerging tool. We describe the performance of AS-OCT in a paediatric population.MethodsA mixed-methods prospective study, using routine clinical assessment as reference standard, and AS-OCT, with Tomey CASIA2 or Heidelberg Spectralis HS1, as index test, with data collected on patient perceptions of imaging. Repeatability, diagnostic indices, responsiveness to clinical change and clinical corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…It can be used to predict anterior chamber angle for phakic intraocular lens implantation with deeper, wider and faster scanning of anterior segment combined with sophisticated mathematical modeling, which could greatly reduce the risks associated with the narrowing of the anterior chamber angle postoperatively [ 21 ]. It could also be applied to assess the anterior chamber inflammation with higher resolution images [ 23 , 24 ]. Besides, it has been reported to predict IOL tilt and decentration in modern cataract surgery [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be used to predict anterior chamber angle for phakic intraocular lens implantation with deeper, wider and faster scanning of anterior segment combined with sophisticated mathematical modeling, which could greatly reduce the risks associated with the narrowing of the anterior chamber angle postoperatively [ 21 ]. It could also be applied to assess the anterior chamber inflammation with higher resolution images [ 23 , 24 ]. Besides, it has been reported to predict IOL tilt and decentration in modern cataract surgery [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, varying OCT devices, including time-domain OCT, spectral domain OCT, and swept-source OCT, have been used for studies to assess the anterior chamber cells in uveitis [ 7 , 8 ]. Recent studies have demonstrated the feasibility of AS-OCT for the quantification of anterior chamber cells in children with uveitis [ 25 , 26 ]. The accurate assessment of anterior chamber inflammation needs prolonged time to observe the anterior segment of uveitic eyes; however, younger children may be uncooperative for slit-lamp microscope examination due to the bright illumination of the slit-lamp beam [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the feasibility of AS-OCT for the quantification of anterior chamber cells in children with uveitis [ 25 , 26 ]. The accurate assessment of anterior chamber inflammation needs prolonged time to observe the anterior segment of uveitic eyes; however, younger children may be uncooperative for slit-lamp microscope examination due to the bright illumination of the slit-lamp beam [ 25 , 26 ]. SS-OCT used in this study has the advantage of high scanning speed, leading to a rapid scan time [ 15 , 16 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anterior segment OCT is a relatively new method to quantify cells in the anterior chamber and needs to be standardized for routine use. 31 …”
Section: Clinical Evaluation Monitoring and Imaging Of Uveitis In Chi...mentioning
confidence: 99%